Tolerance as Recognition: Phenomenological and Psychological Considerations - Staiti, Andrea (Itinerari, 2023)
In this paper I argue that tolerance is a form of recognition. In the first section I address Rainer Forst’s respect-conception of tolerance. In the second section I highlight some problems with Forst’s conception, primarily his distinction between ethics and morality. I argue that Forst’s view presents two shortcomings: (1) an abstract characterization of the subject involved in acts of tolerance as split between an ethical and a moral self; (2) an unquestioned adherence to the idea that tolerance requires two components, a negative and a positive stance. In the third section I criticize the two-component view of tolerance and articulate a phenomenological alternative based on a broadly realistic conception of value. On this account, tolerance is based on an act of neutralized valuing in the context of empathy. In the last section I elaborate on this account and argue that tolerance amounts to the recognition of the other’s capacity to achieve autonomous moral insight. We tolerate others because we want them to correct their wrong moral convictions by themselves, knowing that self-correction is superior to external imposition.